2020
DOI: 10.1093/cvr/cvaa110
|View full text |Cite
|
Sign up to set email alerts
|

Towards standardization of echocardiography for the evaluation of left ventricular function in adult rodents: a position paper of the ESC Working Group on Myocardial Function

Abstract: Echocardiography is a reliable and reproducible method to assess non-invasively cardiac function in clinical and experimental research. Significant progress in the development of echocardiographic equipment and transducers has led to the successful translation of this methodology from humans to rodents, allowing for the scoring of disease severity and progression, testing of new drugs, and monitoring cardiac function in genetically modified or pharmacologically treated animals. However, as yet, there is no sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 116 publications
(133 reference statements)
0
84
0
Order By: Relevance
“…In the metoprolol subgroup, mice were also anaesthetised to undergo TTE just before starting drinking water + metoprolol, which corresponds to 10 days before chemotherapy. Two‐dimensional short‐axis M‐mode echocardiography 15 was performed to measure left ventricular (LV) end‐systolic diameter, LV end‐diastolic diameter, LV septal and posterior wall thickness in diastole and systole, and LV end‐systolic and end‐diastolic volumes to calculate LVEF according to Quinones et al 16 . Heart rate was also assessed during TTE.…”
Section: Methodsmentioning
confidence: 99%
“…In the metoprolol subgroup, mice were also anaesthetised to undergo TTE just before starting drinking water + metoprolol, which corresponds to 10 days before chemotherapy. Two‐dimensional short‐axis M‐mode echocardiography 15 was performed to measure left ventricular (LV) end‐systolic diameter, LV end‐diastolic diameter, LV septal and posterior wall thickness in diastole and systole, and LV end‐systolic and end‐diastolic volumes to calculate LVEF according to Quinones et al 16 . Heart rate was also assessed during TTE.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the small size of the rat heart and the fast heart rate, echocardiography is systematically used in the evaluation of rat heart function (12). Data for 2 main indices of LV contractility were extracted from the list of studies.…”
Section: Methodsmentioning
confidence: 99%
“…x 100 (13) or from the equation: EF (%) = (LVEDV-LVESV)/LVEDV x 100, where LVEDV is the LV end-diastolic volume and LVESV is LV end-systolic volume (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study’s main goal was to describe the diastolic function alterations occurring before and after pressure overload relief. For this reason, we used the E/é ratio as one of the main outputsof the present study since it is a well known surrogate marker of diastolic dysfunction and elevated filling pressures in clinical [ 25 , 26 ] and in pre-clinical [ 27 ] setting. However, compared to the existing literature, similar mouse studies have shown systolic dysfunction and LV dilation at earlier time points after aorta constriction [ 28 , 29 ], which might be explained by the differences between strains and mainly by the degree of aortic constriction [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%